FAKTOR-FAKTOR PENYEBAB PERCAYANYA MASYARAKAT PADA PENGOBATAN BADEWO DI DESA PAUH KECAMATAN BONAI DARUSSALAM KABUPATEN ROKAN HULU - Habibi Rahim; Zahirman Zahirman; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was based on the culture and tradition that was very thick in people’s lives at pauh village, one of the ceremonies of treatment rituals that exist in this community which means to be hired, it came from the word dewa. Bonai community considers deo as a sprits or equivalent to mambang, elves, genie, devils, ghosts and so on, which can help in treating a disease. This treatment ritual call in supernatural beings, spirits that could curing illness. Badewo’s rituals are used for curing diseasess that cannot be detected by the medical, such as disease, black magic, api tuju, and other magic diseases and shamans or kumantan plays an important role in leading the Badewo ritual ceremony. The formulation of the problem in this research was why the people still believe in Badewo ritual at Pauh village, Bonai Darussalam District, Rokan Hulu Regency. The purpose of this research was to find out what factors cause the Bonai tribe community in Bonai Darussalam district, Rokan Hulu regency to believe in Badewo treatment. The informants was a traditional leaders, ninik mamak, village community leaders and pauh village people. This research used a qualitative approach. Data colection techniques using observation, interviews, and documentation methods. Data analysis techniques used data collection, data reduction, data presesentation and conclusions. So community still believed in the treatment of Badewo.Key Words: Belief, Badewo, Bonai